2019
DOI: 10.1542/peds.2019-1576
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Distribution of Child Psychiatrists in the United States: 2007–2016

Abstract: BACKGROUND: Historically, there has been a shortage of child psychiatrists in the United States, undermining access to care. This study updated trends in the growth and distribution of child psychiatrists over the past decade. METHODS: Data from the Area Health Resource Files were used to compare the number of child psychiatrists per 100 000 children ages 0 to 19 between 2007 and 2016 by state and county. We also examined sociodemographic characteristics associated with the density of child psychiatrists at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(78 citation statements)
references
References 35 publications
0
78
0
Order By: Relevance
“…The variation shown in Table 2 raises the question of what is driving these area-level variations? A hypothesis raised in the literature is that shortages of qualified mental health professionals are an important determinant of treatment (16,17). Shortages may leave primary care physicians providing mental health care, even though many pediatricians report that they are uncomfortable in this role (18).…”
Section: Resultsmentioning
confidence: 99%
“…The variation shown in Table 2 raises the question of what is driving these area-level variations? A hypothesis raised in the literature is that shortages of qualified mental health professionals are an important determinant of treatment (16,17). Shortages may leave primary care physicians providing mental health care, even though many pediatricians report that they are uncomfortable in this role (18).…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the question: how many child psychiatrists do we need? The American Academy of Child and Adolescent Psychiatry estimates that 47 child psychiatrists per 100 000 children would be sufficient, which is quadruple the rate found by McBain et al 1,7 The recently published Health Resources and Services Administration (HRSA) "Behavioral Health Workforce Projections, 2016-2030" made the unsubstantiated determination that at most, the demand for child psychiatric services in 2016 exceeded the supply by 20%. 8 Assuming that the child psychiatrist shortage is closer to what American Academy of Child and Adolescent Psychiatry estimates, the current rate of increase will not meet the need for child psychiatric services over the next decade.…”
mentioning
confidence: 95%
“…Wait times for new appointments can be many months, and families may be required to travel long distances. In the article "The Growth and Distribution of Child Psychiatrists in the United States: 2007-2016" in this issue of Pediatrics, McBain et al 1 evaluate whether we have made any progress in expanding the child psychiatry workforce, both in number and distribution. They found that from 2007 to 2016, the number of child psychiatrists increased by 21%, and the number of children in the United States declined slightly.…”
mentioning
confidence: 99%
“…More than 70% have no child psychiatrists. 11 Additionally, a majority of mental health treatment facilities do not provide behavioral health care services for children with ASD. 12 However, there is a paucity of information regarding whether insurance mandates have impacted workforce availability.…”
mentioning
confidence: 99%
“…13 We evaluated the effect of state insurance mandates on workforce supply of three types of health care providers that commonly provide services to children with ASD (BCBAs, child psychiatrists, and pediatricians) over a 15-year period (2003-2017) during which 44 states introduced mandates. We anticipated mandates would be associated with a modest increase in BCBAs 14 but unrelated to supply of child psychiatrists and pediatricians because these latter roles are often overwhelmed by existing patient volume 11,15 and children with ASD likely represent a small percentage of their patient population.…”
mentioning
confidence: 99%